The use of inulin-type fructans improves stool consistency in constipated children. A randomised clinical trial: pilot study. (4th July 2017) - Closa-Monasterolo, Ricardo; Ferré, Natalia; Castillejo-DeVillasante, Gemma; Luque, Veronica; Gispert-Llaurado, Mariona; Zaragoza-Jordana, Marta; Theis, Stephan; Escribano, Joaquin
Abstract: Background: Constipation is a common disorder in children. Objective: The objective of this study is to assess the beneficial effects of a daily supplementation with Orafti ® inulin‐type fructans in 2–5 year old constipated children. Methods: Double‐blind, randomised, placebo‐controlled parallel group trial where constipated children received two doses of 2 g Orafti ® inulin‐type fructans (OF:IN) or placebo (maltodextrin) for 6 weeks. Primary outcome was stool consistency. Secondary outcomes were stool frequency and gastrointestinal symptoms. Results: Twenty-two children were included, 17 completed the study protocol (nine and eight for the control and the OF:IN group, respectively). Results showed that Orafti ® inulin‐type fructans supplemented children had softer stools ( p  = .003). The longitudinal analysis showed no significant changes in controls, whereas supplemented children increased their stool consistency from 2.2 to 2.6 on the modified Bristol scale for children (five items instead of seven) ( p  = .040). Conclusions: Prebiotic inulin‐type fructans supplementation improves stool consistency in constipated 2–5-year old children. Clinicaltrials.gov, with number NCT02863848.